To transform the linear equation 7x + -2y = -6 to slope-intercept form, follow these steps:
1. Begin by isolating the term with the variable y on one side of the equation. We'll move the 7x term to the other side:
-2y = -7x - 6
2. Now, divide both sides of the equation by -2 to solve for y:
y = (-7x - 6) / -2
3. Simplify the right side of the equation:
y = (7/2)x + 3
Therefore, the linear equation 7x + -2y = -6 is transformed to slope-intercept form as y = (7/2)x + 3.
transform the liner equation 7x + -2y = -6 to slop-intercept form
1 answer